Formal Education Versus Learning-by-Doing - Frédéric Gavrel; Isabelle Lebon; Thérèse Rebière (Institute for the Study of Labor (IZA), 2014)
The efficiency of educational choices is studied in a search-matching model where individuals face a tradeoff: acquiring formal education or learning while on the job. When their education effort is successful, newcomers directly obtain a high-skill job; otherwise, they begin with a low-skill job, learn-by-doing and then search while on-the-job for a high-skill job. Low-skill firms suffer from hold-up behavior by high-skill firms. The low-skill sector is insufficiently attractive and individuals devote too much effort to formal education. A self-financing tax and subsidy policy restores market efficiency.
Keywords: H21; I20; J21; J64; J68; 330; formal education; learning-by-doing; market efficiency; on-the-job search; search unemployment